Diets of double‐crested cormorants in the Lake Winnebago System, Wisconsin. (9th November 2020) - Koenigs, Ryan P.; Dembkowski, Daniel J.; Lovell, Charles D.; Isermann, Daniel A.; Nickel, Adam D.
Abstract: Double‐crested cormorant Phalacrocorox auritus Lesson (cormorant) populations have increased throughout the Great Lakes region of North America causing concern related to the impact of cormorant predation on fish communities. A recent decline in yellow perch Perca flavescens (Mitchill) abundance within the Lake Winnebago System, Wisconsin, USA, prompted an assessment of cormorant diets to evaluate potential effects of cormorant predation on the sportfish community. Diets were collected from 883 cormorants (417 from Lake Winnebago and 466 from Lake Butte des Morts) between 2015 and 2017. Cormorant diets on both waterbodies consisted mostly of freshwater drum Aplodinotus grunniens Rafinesque and gizzard shad Dorosoma cepedianum (Lesueur). Yellow perch and walleye Sander vitreus (Mitchill) observations were infrequent and represented < 5% of cormorant diets by weight each year. Under current conditions, cormorant predation likely has minimal impact on the Lake Winnebago sportfish community, but more research is needed to assess potential impacts on Lake Butte des Morts.